Pengaruh Model Problem Based Learning Berbantuan Color Coding Terhadap Kemampuan Literasi Sains Peserta Didik Pada Pembelajaran Biologi di SMAN 1 Pangkalan: Penelitian - Ostri Wahyuni; Helendra; Muhyiatul Fadilah; Fitri Olvia Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education plays an important role in preparing students to face the challenges of the 21st century, one of which is through improving scientific literacy. However, the results of a pre-research questionnaire showed that 70.1% of phase E students at SMAN 1 Pangkalan Koto Baru rarely read materials or work on questions based on scientific literacy, and 50.5% of students had never heard of the term scientific literacy. This has impacted students’ low ability to explain scientific phenomena and interpret data scientifically. Therefore, learning innovations are needed, such as the application of the Problem Based Learning (PBL) model assisted by color coding to improve students’ scientific literacy skills, particularly on the topic of environmental change. This research is quantitative research with an experimental design using a Randomized Control-Group Posttest Only Design. The study population consisted of all phase E students at SMAN 1 Pangkalan, with a sample of two classes randomly selected. The experimental class received treatment using the PBL model assisted by color coding, while the control class used a conventional learning model. Data were collected through a scientific literacy ability posttest and analyzed using normality tests, homogeneity tests, and hypothesis testing. The results showed that the implementation of the Problem Based Learning model assisted by color coding had a significant effect on improving students’ scientific literacy skills. This is indicated by the average posttest score of the experimental class, which was 79.43, higher than that of the control class, which was 68.22. This study concludes that the PBL model assisted by color coding is effective in improving the scientific literacy skills of phase E students on the topic of environmental change at SMAN 1 Pangkalan.